Behavior of austempered ductile iron (ADI) grinding using different MQL dilutions and CBN wheels with low and high friability - Silva, Andrigo Elisiario da [UNESP]; Lopes, Jose Claudio [UNESP]; Daniel, Douglas Maiochi [UNESP]; Moraes, Douglas Lyra de [UNESP]; Garcia, Mateus Vinicius [UNESP]; Ribeiro, Fernando Sabino Fonteque; Mello, Hamilton Jose de [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
This work aimed to study the application of minimum quantity of lubricant (MQL) with the addition of water, respecting the proportions 1:0, 1:5, 1:10, and 1:20 oil-water, in the cylindrical grinding of austempered ductile iron (ADI). Also, two cubic boron nitride (CBN) grinding wheels, with distinct friability levels, were used. The analysis of surface roughness (Ra), roundness error, G-ratio, grinding power consumed, specific grinding energy, microhardness, and microstructure was done using confocal and optical microscopy. The results show that the addition of water to the MQL mixture significantly improves its characteristics. Thus, MQL 1:5 (oil-water) produced the best results among the alternative methods analyzed. Also, all MQL variations did not produce microstructural change or thermal damage to the workpieces. Besides, the less friable grinding wheel (CBN GL) produced better surface quality of the workpieces and caused less wheel wear compared with the more friable wheel (CBN GS). On the other hand, the more friable wheel used less power during the grinding.
Keywords: Grinding; MQL; CBN; Austempered ductile iron; Diluted MQL